Evaluation of Blood Plasma Coagulability by Laser Speckle Correlation; Biomedical Engineering; Vol. 52, iss. 3 - Li Lin; Sytnik Yu. D. Yuliya Dmitrievna; Gubarev F. A. Fedor Aleksandrovich; Pekker Ja. S. Jakob Semenowitsch (2018, 2018)
Title screen